2021
DOI: 10.52162/jie.2021.004.02.2
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Aquilaria Species as Potential of Pharmacological

Abstract: One of the plants that is rich in benefits is from the genus Aquilaria spp. which is known to be able to produce agarwood resin. This genus includes 47 species, of which the four main species are Aquilaria malaccensis, Aquilaria subintegra, Aquilaria crassna and Aquilaria sinensis. Aquilaria species are known to have a wide spectrum of pharmacological activity and have been reported in many studies, including activity, anticancer, anti-inflammatory, AChE inhibitor (Acetylcholinesterase), anti-proliferative, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A. malaccensis is used in traditional herbal medicine to relieve epilepsy, rheumatism, inflammation, weakness, bronchitis, and in the treatment of snake bites. 9 And recently, in vivo and in vitro studies reported the phytomedicinal uses of agarwood of anti-inflammatory, immunomodulatory, anti-obesity, antidiabetic activity in asthma, neurological disorders, stress and anxiety reduction, cancer, and others. 10 While A. malaccensis and agarwood have shown potential in various areas of traditional medicine, scientific research is still ongoing to validate these claims and to better understand the specific bioactive compounds responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…A. malaccensis is used in traditional herbal medicine to relieve epilepsy, rheumatism, inflammation, weakness, bronchitis, and in the treatment of snake bites. 9 And recently, in vivo and in vitro studies reported the phytomedicinal uses of agarwood of anti-inflammatory, immunomodulatory, anti-obesity, antidiabetic activity in asthma, neurological disorders, stress and anxiety reduction, cancer, and others. 10 While A. malaccensis and agarwood have shown potential in various areas of traditional medicine, scientific research is still ongoing to validate these claims and to better understand the specific bioactive compounds responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%